2018
DOI: 10.1111/jspn.12227
|View full text |Cite
|
Sign up to set email alerts
|

Parent, school, and peer factors related to U.S. adolescents’ diet and exercise

Abstract: Purpose Adolescent obesity is a significant public health problem in the United States. Developing interventions to prevent or improve adolescent obesity may positively affect physical and mental health across the lifespan. However, to ensure that interventions are effective, influential factors must first be identified. The purpose of this study was to examine associations among parent‐, school‐, and peer‐related factors and diet and physical activity of the adolescents in the United States. Design and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…In the international HBSC 2018, the same association between socioeconomic status of families and peer support was revealed; in more than half of the countries, high FAS was positively associated with better peer relationships and, in some countries, this association was found highly noticeable. Moreover, socioeconomic status has been previously reported as a factor that might modulate the physically active lifestyle of adolescents [41,[46][47][48][49][50]. The international HBSC 2018 data showed that socioeconomic status may have an impact on physical activity levels among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In the international HBSC 2018, the same association between socioeconomic status of families and peer support was revealed; in more than half of the countries, high FAS was positively associated with better peer relationships and, in some countries, this association was found highly noticeable. Moreover, socioeconomic status has been previously reported as a factor that might modulate the physically active lifestyle of adolescents [41,[46][47][48][49][50]. The international HBSC 2018 data showed that socioeconomic status may have an impact on physical activity levels among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Peers are the most important objects of interpersonal communication among adolescents, and the improvement of peer communication skills is an important aspect of adolescent social development, and adolescents actively or passively bear the influence and even pressure from peers due to the needs of selfdevelopment and independent consciousness [15]. A large number of studies have found that adolescents' eating behavior is related to their peers [16][17]. Peers influence adolescent food choices because they influence each other's behaviors, attitudes, behaviors, and preferences [18].…”
Section: Discussionmentioning
confidence: 99%
“…In total, nine studies looked at leisure physical activity. Six studies reported no significant findings: two were conducted in the US, one of good (38) and one of fair quality (39), looking at 10-17 and 10-19 year olds respectively, one (good) study from Italy (40), looking at 14-17 year olds, one (fair) in Switzerland ( 41), looking at 13-14 year olds, using parent-report, and two poor quality studies, one in Australia ( 42), looking at 13-17 year olds, and one in Canada ( 43), looking at 13-15 year olds.…”
Section: Low Moderate or High Levels Of Physical Activitymentioning
confidence: 99%